2014
DOI: 10.1016/j.expneurol.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Parkinson's disease in monkeys for translational studies, a critical analysis

Abstract: The non-human primate MPTP model of Parkinson’s disease is an essential tool for translational studies. However, the currently used methodologies to produce parkinsonian monkeys do not follow unified criteria, and the applied models may often fall short of reproducing the characteristics of patients in clinical trials. Pooling of data from the parkinsonian monkeys produced in our Centers provided the opportunity to evaluate thoroughly the behavioral outcomes that may be considered for appropriate modeling in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 54 publications
(66 reference statements)
2
46
0
Order By: Relevance
“…On a behavioral point of view, all four animals were differently affected by the MPTP lesion (Figure 2; based on the semi-quantitative Schneider score), confirming the large inter-individual variability previously reported in the literature and representing an obvious limitation of the non-human primate MPTP model [34,[46][47][48]. Such observed inter-individual variability places the present experimental model within the standards in the field (animal PD models).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On a behavioral point of view, all four animals were differently affected by the MPTP lesion (Figure 2; based on the semi-quantitative Schneider score), confirming the large inter-individual variability previously reported in the literature and representing an obvious limitation of the non-human primate MPTP model [34,[46][47][48]. Such observed inter-individual variability places the present experimental model within the standards in the field (animal PD models).…”
Section: Discussionsupporting
confidence: 86%
“…One may speculate that such sprouting of residual dopaminergic projection contributes to functional recovery, in cooperation with non-dopaminergic compensatory mechanisms [44,45]. The observation in monkey Mk-LY of a modest decrease of striatal 18F-DOPA uptake post-MPTP lesion (17%) may possibly be interpreted as a resistance to MPTP [46], at least to some extent.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, in the context of hESC-based therapy for PD, preclinical testing of functional stability will likely depend on the stability of parkinsonism in nonhuman primate models [51].…”
Section: Resultsmentioning
confidence: 99%
“…The low-dose MPTP monkey model (Bezard et al, 1997) is the model of choice for translational study because it presents a parkinsonian syndrome characterized by all critical aspects of PD, including a slow progressive evolution of symptoms, e.g., it replicates the typical motor symptoms used for primary clinical diagnosis of parkinsonism with response to classical DA therapy (Stephenson et al, 2005), characteristic pattern of nigrostriatal denervation observed in PD patients (Gibb and Lees, 1991;Perez-Otano et al, 1994), early and long-lasting non-motor symptoms (Poewe, 2008;Vezoli et al, 2011;Fifel et al, 2014;Swallow et al, 2016), and increased α-synuclein expression in the pigmented cells of the SN (substantia nigra; Purisai et al, 2005). However, even if those inclusion bodies appears in the same sites as for Lewy bodies in PD, e.g., SN, they do not express typical Lewy body features as found in human PD patients (Forno et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus on preclinical investigations done in the gold standard NHP MPTP model (Emborg, 2007;Potts et al, 2014). We provide a non-exhaustive review of different procedures using transplantation of various cell sources as a therapeutic approach in the NHP MPTP model of PD and provide an update on linked therapeutic behavioral and functional outcomes.…”
Section: Introductionmentioning
confidence: 99%